Campus Canopy, 1935-04-10 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1935)
Glee Club Concert Proves Success -- Student Elections -- May Day-Play Day Set for April 27th -- Mildred Seydell To Speak Here -- Officers of S.G.A Report on Meeting -- Program Arranged for Delegates
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals